THE EFFECT OF OYSTER MUSHROOM TO MIREPOIX RATIO ON THE PHYSICAL PROPERTIES AND SENSORY QUALITY OF MUSHROOM SEASONING POWDER - Anastasia Clarisa Sadono; Sachriani Sachriani; Alvina Fadila Maulida (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aimed to investigate the effect of oyster mushroom (Pleurotus ostreatus) to mirepoix ratio on the physical properties and sensory quality of mushroom seasoning powder as a natural alternative to monosodium glutamate (MSG). The study was motivated by the growing consumer demand for healthier, natural food products and the persistent problem of post-harvest surplus of oyster mushrooms at the farm level. An experimental method was employed with three ratio treatments of oyster mushroom to mirepoix namely 70:30, 60:40, and 50:50 alongside a control treatment (100:0). Physical properties assessed included acidity (pH) and total dissolved solids (°Brix), while sensory quality evaluation covered color, oyster mushroom aroma, mirepoix aroma, umami taste, oyster mushroom taste, and texture, tested under both dry and dissolved conditions. Validation testing was conducted by five expert panelists and sensory quality testing by 45 semi-trained panelists. Data were analyzed using one-way ANOVA for physical properties and the Kruskal-Wallis test for sensory quality, followed by post-hoc tests where significant effects were found. Results indicated that the ratio significantly affected pH (Fcount = 174.889 > Ftable = 4.066) but had no significant effect on °Brix. The 70:30 formulation yielded the optimal sensory profile: pale yellow-cream color, dominant mushroom aroma and taste, strong umami, fine powder texture, and pH closest to neutral.